101 coaching strategies and techniques - McMahon, Gladeana, 1954-; Archer, Anne, 1960- (Essential coaching skills & knowledge., 2010)
Offers practical strategies to help the coach with their work, providing an explanation of the strategy together with potential pitfalls and solutions.